Brain activity underlying visual perception and attention as inferred from TMS-EEG: a review. - Taylor, P; Thut, G (2012)
Probing brain functions by brain stimulation while simultaneously recording brain activity allows addressing major issues in cognitive neuroscience. We review recent studies where electroencephalography (EEG) has been combined with transcranial magnetic stimulation (TMS) in order to investigate possible neuronal substrates of visual perception and attention. TMS-EEG has been used to study both pre-stimulus brain activity patterns that affect upcoming perception, and also the stimulus-evoked and task-related inter-regional interactions within the extended visual-attentional network from which attention and perception emerge. Local processes in visual areas have been probed by directly stimulating occipital cortex while monitoring EEG activity and perception. Interactions within the attention network have been probed by concurrently stimulating frontal or parietal areas. The use of tasks manipulating implicit and explicit memory has revealed in addition a role for attentional processes in memory. Taken together, these studies helped to reveal that visual selection relies on spontaneous intrinsic activity in visual cortex prior to the incoming stimulus, their control by attention, and post-stimulus processes incorporating a re-entrant bias from frontal and parietal areas that depends on the task.